The microbial guardians: Unveiling the role of gut microbiota in shaping neurodegenerative disease - Nour Abou Izzeddine; Kawsar Ahmad; Christine Bacha; Maria Jabbour; Mouin Najjar; Sethrida Salhab; Hilda E. Ghadieh; Amjad Kanaan; Sami Azar; Ziad Abi Khattar; Frederic Harb (IBRO Neuroscience Reports)
The gut microbiota, a complex community of microorganisms residing in the digestive tract, plays a pivotal role in human health. Recent studies have highlighted its significant impact on neurodegenerative diseases, conditions that pose profound challenges to affected individuals and society at large. This review explores the intricate relationship between gut microbiota and the progression of neurodegenerative disorders, such as Alzheimer's disease, Parkinson's disease, Huntington’s disease, and Amyotrophic Lateral Sclerosis. We delve into the dynamic ecosystem of gut microbiota, examining factors influencing its composition and the bidirectional communication established via the gut-brain axis. Emerging evidence suggests that gut microbiota can modulate neurodegenerative disease progression through mechanisms including inflammatory responses, production of neuroactive substances, and regulation of neurotransmitters. Furthermore, we discuss the potential therapeutic implications of targeting gut microbiota with probiotics, prebiotics, and postbiotics. While promising, these interventions face challenges and limitations that must be addressed through ongoing research. Understanding the role of gut microbiota in neurodegenerative diseases is crucial for developing innovative therapeutic strategies and improving patient outcomes.